Mechanisms for Activating Family Guidance in the Emirati Society in light of the Digital Environment - Al-Mutawa, Aisha Abdullah (Journal of Ecohumanism, 2025)
The study aimed to identify the mechanisms for activating family guidance in the Emirati society in light of the digital environment, by identifying the reality of family guidance, the elements of family guidance quality, the mechanisms for activating family guidance, and the most important proposals for activation in the Emirati society in light of the digital environment. This study is one of the descriptive studies that aim to identify the mechanisms for activating family counseling in the Emirati society in light of the digital environment, as a field study applied to a sample of workers in family counseling centers in the city of Sharjah in the United Arab Emirates. In line with the type of study, the researcher relied on the social survey method with a sample, for a sample of (90) workers in those centers, which were represented in (Emirates Family Counseling Association Center, Family Development Center, Hamsa Family Counseling Center, Family Counseling Center). The results of the study confirmed that the realities of family counseling in the Emirati society in light of the digital environment may be represented in: the interest of the Emirati family in encouraging its members to request family counseling, telephone family counseling helped to request family counseling in sensitive problems within the family, increased interest in qualifying those about to get married in light of the spread of electronic family counseling, and that the components of the quality of family counseling in the Emirati society in light of the digital environment may be represented in: the use of effective artificial intelligence programs to provide family counseling in light of the digital environment, training family counselors on how to use technology in Family counseling, availability of technical skills among family counselors in the digital environment, and that the most important mechanisms for activating family counseling in the Emirati society in the digital environment, may be represented in: strategic planning for the future of family counseling in the digital environment, effective social marketing of family counseling programs in the digital environment, training family counselors on the latest artificial intelligence programs in the field of family counseling, and that the most important proposals for activating family counseling in the Emirati society in the digital environment, may be represented in: providing trained and specialized human capabilities to work in the field of family counseling in the digital environment, estimating the needs of the Emirati family for family counseling programs in the digital environment, spreading the culture of family counseling in the digital environment, benefiting from successful international experiences in the field of family counseling in the digital environment, effective social marketing of successful family counseling programs in the digital environment.